Cooperative Principle Used by Chris Gardner in “The Pursuit of Happyness” Movie - Oisi Sapalakkai (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study is to find out what maxims are used by Chris Gardner, what maxims are flouted by Chris, and what implicature can be interpreted by flouting the maxims in the business conversation in The Pursuit of Happinessmovie. The source of the data was the film and the transcript, and the data were taken from Chris’ utterancesin the five chosen scenes showing the process of Chris’s success in pursuing his happiness in his life. The findings revealed that he mostly followed the maxim of manner and the least was maxim of quality. He also flouted the maxim of quality and the leastwas maxim of manner. From the flouting of the maxims, there was implicature that could be interpreted which was to create a good relation, to get a good chance, and to fulfill Chris’s will to be one employee in Dean Witter Reynolds-Resource Dept. which is the beginning of his success in his life. In conclusion, the flouting of the maxims was part of Chris’s effort in his life that gave contribution to his success, andit is proved through Chris’ utterances in the five chosen scenes.